2023
DOI: 10.1186/s12938-023-01133-8
|View full text |Cite
|
Sign up to set email alerts
|

Home-based upper limb stroke rehabilitation mechatronics: challenges and opportunities

Abstract: Interest in home-based stroke rehabilitation mechatronics, which includes both robots and sensor mechanisms, has increased over the past 12 years. The COVID-19 pandemic has exacerbated the existing lack of access to rehabilitation for stroke survivors post-discharge. Home-based stroke rehabilitation devices could improve access to rehabilitation for stroke survivors, but the home environment presents unique challenges compared to clinics. The present study undertakes a scoping review of designs for at-home upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 119 publications
1
1
0
Order By: Relevance
“…We refined the device's appearance, and also added a passive DoF for wrist pronosupination, a movement highly recommended by therapists (Rätz et al, 2021b ), by allowing the entire device to be tilted around its longitudinal axis. The combination of passive and active degrees of freedom is in line with the recommendations of Forbrigger et al ( 2023a ), who suggested this concept to reduce cost while still providing high functionality. We thus satisfied all the required device improvements that we defined based on the first concept (see Section 2.1.1).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We refined the device's appearance, and also added a passive DoF for wrist pronosupination, a movement highly recommended by therapists (Rätz et al, 2021b ), by allowing the entire device to be tilted around its longitudinal axis. The combination of passive and active degrees of freedom is in line with the recommendations of Forbrigger et al ( 2023a ), who suggested this concept to reduce cost while still providing high functionality. We thus satisfied all the required device improvements that we defined based on the first concept (see Section 2.1.1).…”
Section: Discussionsupporting
confidence: 77%
“…However, both group therapy and at-home rehabilitation require adequate tools that deliver high-dosage training and ensure patient engagement in minimally supervised (group therapy) or unsupervised environments (home rehabilitation). Sensorized or robotic devices in combination with interactive gamified exercises are promising candidates to drive this paradigm shift (Chen et al, 2019 ; Handelzalts et al, 2021 ; Lambercy et al, 2021 ; Forbrigger et al, 2023a ). The effectiveness of robot-based group therapy in providing high dosage high-intensity therapy has already been demonstrated (e.g., Hesse et al, 2014 ), while the feasibility of sensorized or robotic devices to deliver high dosage in self-guided therapies at home has been largely endorsed, (e.g., Sivan et al, 2014 ; Wittmann et al, 2016 ; Hyakutake et al, 2019 ; McCabe et al, 2019 ; Rozevink et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%